2019
DOI: 10.1371/journal.pone.0206895
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the quality of distal radius systematic reviews: Methodology and reporting assessment

Abstract: BackgroundMany systematic reviews (SRs) have been published about the various treatments for distal radius fractures (DRF). The heterogeneity of SRs results may come from the misuse of SR methods, and literature overviews have demonstrated that SRs should be considered with caution as they may not always be synonymous with high-quality standards. Our objective is to evaluate the quality of published SRs on the treatment of DRF through these tools.MethodsThe methods utilized in this review were previously publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…Regarding non-surgical treatment, a Cochrane review based on randomized controlled trials has concluded that controversy remains in terms of the type of immobilization to be applied after the initial fracture reduction [ 4 ]. A recent overview of systematic reviews about the treatment of DRF in adults demonstrated that only two studies were on conservative treatment and none of them underwent meta-analysis [ 5 ]. A major systematic review on the topic was carried out by Handoll et al which justified the absence of meta-analysis due to the low quality and heterogeneity in terms of interventions compared and outcome measurement of the included trials [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding non-surgical treatment, a Cochrane review based on randomized controlled trials has concluded that controversy remains in terms of the type of immobilization to be applied after the initial fracture reduction [ 4 ]. A recent overview of systematic reviews about the treatment of DRF in adults demonstrated that only two studies were on conservative treatment and none of them underwent meta-analysis [ 5 ]. A major systematic review on the topic was carried out by Handoll et al which justified the absence of meta-analysis due to the low quality and heterogeneity in terms of interventions compared and outcome measurement of the included trials [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of unequivocal results from previous studies could partly be explained by studies being under-powered and study population heterogeneous with regards to fracture patterns and patient age [7]. Numerous literature reviews have been performed for comparison of treatment methods for DRFs [8] but only few regard populations of higher ages [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, as found in the previous study, the quality of reporting and methodology for orthopaedic sports medicine remains greater, if not in line, with orthopaedics in general. Zhi et al 19 reported an average PRISMA score of 77 of leading orthopaedic journals, Belloti et al 20 found an average PRISMA and AMSTAR scores of 59 in systematic reviews on distal radius fractures, and Sathish and Eswar 7 published a AMSTAR score of 68 of reviews in spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 19 reported an average PRISMA score of 77 of leading orthopaedic journals, Belloti et al. 20 found an average PRISMA and AMSTAR scores of 59 in systematic reviews on distal radius fractures, and Sathish and Eswar 7 published a AMSTAR score of 68 of reviews in spine surgery.…”
Section: Discussionmentioning
confidence: 99%